2012
DOI: 10.1152/ajpcell.00355.2011
|View full text |Cite
|
Sign up to set email alerts
|

A non-cross-bridge, static tension is present in permeabilized skeletal muscle fibers after active force inhibition or actin extraction

Abstract: When activated muscle fibers are stretched, there is a long-lasting increase in the force. This phenomenon, referred to as "residual force enhancement," has characteristics similar to those of the "static tension," a long-lasting increase in force observed when muscles are stretched in the presence of Ca(2+) but in the absence of myosin-actin interaction. Independent studies have suggested that these two phenomena have a common mechanism and are caused either by 1) a Ca(2+)-induced stiffening of titin or by 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 35 publications
10
51
0
Order By: Relevance
“…Another study has reported that an increase in calcium concentration reduced rather than increased titin-actin interaction (Stuyvers et al, 1998). In agreement with these results, Cornachione and Rassier (2012) observed that static tension was preserved after depletion with gelsolin of actin filaments, suggesting that titin-actin binding is not involved.…”
Section: Physiological Role Of Static Stiffnesssupporting
confidence: 65%
See 2 more Smart Citations
“…Another study has reported that an increase in calcium concentration reduced rather than increased titin-actin interaction (Stuyvers et al, 1998). In agreement with these results, Cornachione and Rassier (2012) observed that static tension was preserved after depletion with gelsolin of actin filaments, suggesting that titin-actin binding is not involved.…”
Section: Physiological Role Of Static Stiffnesssupporting
confidence: 65%
“…Later static stiffness was observed in intact mammalian skeletal muscle fibres (Roots et al, 2007;Colombini et al, 2009;Nocella et al, 2012Nocella et al, , 2014 and in permeabilized fibres (Campbell and Moss, 2002;Cornachione and Rassier, 2012). More recently, it has also been shown in skeletal muscle myofibrils .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…There is one study that showed an increase in stiffness after stretch when compared to isometric contractions produced at corresponding lengths [16]. However, the increase in stiffness was attributed to non-cross bridges structures (see §3a(ii)).…”
Section: Mechanisms Of Force Enhancementmentioning
confidence: 99%
“…While some of these studies focused on the residual force enhancement [10,11,14], others aimed to evaluate the molecular aspects of muscle contraction [15][16][17][18]. The latter studies still added important data for a better understanding of the mechanism of the force enhancement.…”
Section: Introductionmentioning
confidence: 99%